2010
DOI: 10.1016/j.jad.2009.10.028
|View full text |Cite
|
Sign up to set email alerts
|

Non-suicidal self-injurious behavior, endogenous opioids and monoamine neurotransmitters

Abstract: Background-Self inflicted injury, including cutting or burning, is the most frequent reason for psychiatric visits to medical emergency departments. This behavior, particularly when there is no apparent suicidal intent, is poorly understood from both biological and clinical perspectives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
106
2
20

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(136 citation statements)
references
References 86 publications
(76 reference statements)
8
106
2
20
Order By: Relevance
“…Dysregulation of the endogenous opioid system has been implicated in nonsuicidal self-harm [Tiefenbacher et al 2005;Schmahl et al 2002], interpersonal vulnerabilities and social attachments [Panksepp et al 1978], all of which are implicated to some degree in the clinical spectrum of BPD. Evidence for this has been demonstrated in human studies, revealing altered opioid neurotransmission associated with negative affect [Zubieta et al 2003[Zubieta et al , 2002, altered opioid levels in patients with a history of self-harm [Stanley et al 2009;Sandman et al 1997;Coid et al 1983], and genetic single nucleotide polymorphisms in the m-opioid receptor gene associated with identity disturbance [Stanley and Siever, 2010].…”
Section: Antipsychotic Medicationsmentioning
confidence: 99%
“…Dysregulation of the endogenous opioid system has been implicated in nonsuicidal self-harm [Tiefenbacher et al 2005;Schmahl et al 2002], interpersonal vulnerabilities and social attachments [Panksepp et al 1978], all of which are implicated to some degree in the clinical spectrum of BPD. Evidence for this has been demonstrated in human studies, revealing altered opioid neurotransmission associated with negative affect [Zubieta et al 2003[Zubieta et al , 2002, altered opioid levels in patients with a history of self-harm [Stanley et al 2009;Sandman et al 1997;Coid et al 1983], and genetic single nucleotide polymorphisms in the m-opioid receptor gene associated with identity disturbance [Stanley and Siever, 2010].…”
Section: Antipsychotic Medicationsmentioning
confidence: 99%
“…The EOS in particular has been a special focus of interest in the study of NSSI. Individuals with NSSI have been shown to have lower resting levels of the opioid types β-endorphin and enkephalins compared to individuals without NSSI (Bresin & Gordon, 2013b;Stanley et al, 2010). Another hypothesis that has been put forward is that repeated exposure to childhood abuse habituates the individual to high levels of endogenous opioids (Sher & Stanley, 2009).…”
Section: Neurobiological Mechanismsmentioning
confidence: 99%
“…Furthermore, painful sensations, compared to non-painful sensations, lead to a larger decrease in negative affect for individuals with NSSI (Bresin & Gordon, 2013a). It has been shown that repeated NSSI activates the endogenous reward neurocircuitry (Bresin & Gordon 2013a, 2013bOsuch & Payne, 2009;Sher & Stanley, 2009;Stanley et al, 2010): "Since endogenous opioids are involved in reward and the regulation of pain and affect, it seems likely that this system is a possible mechanism of affect regulation in NSSI" (Bresin & Gordon, 2013b, p. 376). A unique aspect of NSSI compared to many other 27 functionally equivalent behaviors is the role of blood.…”
Section: How Does Nssi Regulate Emotion?mentioning
confidence: 99%
“…NSSI has been included in the newest version of the Diagnostic and Statistical Manual of Mental Disorders (DSM-5) as a new disorder, and was proved to be a potent risk factor for later suicide attempts [5][6][7], indicating that this problematic behavior deserves more attention. Both intrapersonal and interpersonal risk factors for NSSI have been examined, with most studies focusing on intrapersonal risk factors [8][9][10][11][12][13][14]. Within interpersonal risk factors, invalidating family relationships has been paid much attention [15][16][17].…”
Section: Introductionmentioning
confidence: 99%